2019
DOI: 10.1021/acs.cgd.9b00479
|View full text |Cite
|
Sign up to set email alerts
|

Czochralski Growth, Optical, Scintillation, and Defect Properties of Cu2+ Codoped Lu2SiO5:Ce3+ Single Crystals

Abstract: Divalent cation codoping, such as with Ca 2+ and Mg 2+ , is beneficial for the scintillation performance enhancement of Czochralski-grown Lu 2 SiO 5 :Ce (LSO:Ce) single crystals for nuclear medical imaging applications, but with that benefit comes a tendency toward acentric growth due to the reduced surface tension of the melt. Here, we present a divalent Cu codoping strategy to achieve a simultaneous improvement of light yield, energy resolution, scintillation decay, and afterglow in LSO:Ce single crystals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…The Ce 3+ PL decay time is shortening upon Li + or Cu 2+ co‐doping in the Y 3 Al 5 O 12 (YAG) or Lu 2 SiO 5 (LSO) hosts. [ 44–46 ] However, there, the shortening of the Ce 3+ decay time was accompanied by the increase in light yield (LY) and afterglow. The observed effects were explained by the dissociation of spatially correlated oxygen vacancies ( V O ) and Ce centers or the suppression of V O creation due to Li + co‐doping in LSO:Ce,Li.…”
Section: Resultsmentioning
confidence: 99%
“…The Ce 3+ PL decay time is shortening upon Li + or Cu 2+ co‐doping in the Y 3 Al 5 O 12 (YAG) or Lu 2 SiO 5 (LSO) hosts. [ 44–46 ] However, there, the shortening of the Ce 3+ decay time was accompanied by the increase in light yield (LY) and afterglow. The observed effects were explained by the dissociation of spatially correlated oxygen vacancies ( V O ) and Ce centers or the suppression of V O creation due to Li + co‐doping in LSO:Ce,Li.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to highlight that these high refractory silicates were grown by the CZ method [1-5, 35-37, 39-41]. For example, Ryba-Romanovski et al [1] developed solid state yellow lasers based on (Lu x Gd 1-x ) 2 SiO 5 :Sm crystals by CZ, while Wu et al [41] have recently grown Cu co-doped Ce:Lu 2 SiO 5 crystals at 1.5 mm h −1 using a iridium crucible under nitrogen atmosphere for application as scintillators. Furthermore, other approaches for oxyorthosilicates production have been employed during the last years using different methods, like pulsed laser deposition [42], sol-gel [43] or solid-state diffusional process [44].…”
Section: Oxyorthosilicatesmentioning
confidence: 99%
“…Lutetium oxyorthosilicate (Lu 2 SiO 5 , LSO) has attracted the attention of researchers due to their favorable thermal and optical properties, which make it suitable as host materials to be used in photonics as laser media [3][4][5][6] or scintillators [7,41,59]. The main technique for producing LSO crystals is usually the CZ method.…”
Section: Lutetium Oxyorthosilicate (Lso)mentioning
confidence: 99%
“…As for LYSO:Ce, the typical approach is a partial substitution of the rare earth ions by divalent cations, such as Ca 2+ , Mg 2+ , , which can enhance the LY and shorten the decay time due to the decrease of deep-level traps associated with oxygen vacancies (V O ·· ) and the introduction of Ce 4+ ions . The presence of Ce 4+ bypasses the initial hole capture process of Ce 3+ emission and thus improves the excitation transfer efficiency. ,, It has been found that the codopants (Cu 2+ and Li + ) can reduce the decay time of Lu 2 SiO 5 :Ce crystals, which is due to the enhancement of the thermal ionization of the Ce 3+ 5d 1 state and the suppression of the slow emission of Ce2, which is sixfold coordinated by an oxygen atom. , It thus appears that codoping by the low-valent ion is a promising strategy to improve the scintillation performance of LYSO:Ce crystals.…”
Section: Introductionmentioning
confidence: 99%